PATHOGENIC POTENTIAL OF SEVEN DRECHSLERA SPECIES PREVALENT IN CEREAL SEEDS - K. S. AULAKH, SATVINDER KAUR, A. P. S. MANN* AND (Indian Phytopathology, 2002)
Pathogenicity and toxicity of seven Drechslera species isolated in large numbers from apparently normal looking randomly sampled seeds of cultivated cereals was determined. A fairly large proportion of this was pathogenic as well as toxigenic.